E‐Government systems in South Africa: An infoculture perspective. Issue 4 (30th May 2018) - Singh, Shawren; Travica, Bob
Abstract: The purpose of this study was to investigate challenges surrounding e‐Government systems in South Africa and their origins. Based on interviews with senior managers/senior state administrators as the key method and on qualitative data analysis, challenges were identified within the cultural environment of the senior managers, their positioning in relation to e‐Government systems, organizational processes, and in the policy domain. A specialized cultural analysis based on the informing culture framework was applied in order to deepen understanding of the challenges' origins. It revealed a hybrid of an immature bureaucracy and a mature clan informing culture as deep‐seated aspects of the socio‐organizational context surrounding South African e‐Government systems. The contributions of this research are in advancing theorizing on e‐Government and in helping the senior managers/senior state administrators to develop a better understanding of the cultural environment that they are expected to work in.